A percepção dos farmacêuticos como profissionais de saúde no SUS em Fortaleza-CE - Oliveira, Alex Ferreira de (2008)
The evolution of pharmaceutical extent through Public Health services and clinical context is a global tendency with repercussion on new professional practices development to support the attributions that didn’t exist before. In Brazil the pharmacist role to implement the National Drug Policy and pharmaceutical practices, including pharmaceutical care, in primary health care, is being regulated, causing troubles in working process that go beyond technical aspects. To promote an approximation of this reality, we use an exploitative descriptive study which resorted qualitative research method, with interviews applied to pharmacists and observational techniques applied to professionals and health family centers. The objective was to recognize the local reality and evaluate pharmacists’ perception like health professionals in their routine activities. We visited 12 (92%) of 13 health family centers what have pharmacist working in primary health care pharmacies, of witch 5 (42%) work during 2 turns and 7 (58%) at 3 turns, they have 30 PSF teams to cover their areas and a variable registered professional list according to units needs. We also observed structure problems, lack planning and low level of team work. The pharmacies follow the same problems that we identify in the health family centers, but it works more isolated. We interview 17 (94%) of 18 pharmacists, 13 (76%) women and 4 (24%) men; with age group between 26 and 58 years old. A number of 15 (88%), graduated by Public University, between 1878 and 2006, the major have qualification in biochemistry (53%) and was public servants (82%), with 18 year middle work time. The only post graduation related was expert, concluded by 41% of them. The pharmacist’s perceptions means rubs identifications, related to symbolic and practice categories that raise difficulties the pharmacist’s conception like health professionals and better services promotion. Its essential recover the pharmacist’s self-esteem and promotes a professional guidance to improve actions of health integrality.